Economic report of the President : transmitted to the Congress, January, 1987 : together with the annual report of the Council of Economic Advisers - United States. President - Ronald Regan; Reagan, Ronald; Council of Economic Advisers (U.S.) (Washington, D.C. : United States Government Printing Office, 1987)
The Report covers: Growth and Adjustment in the United States Economy; Budget Control and Tax Reform; Growth, Competitiveness, and the Trade Deficit; Opening International Markets; Toward Agricultural Policy Reform; Risk and Responsibility; Women in the Labor Force.
rpm 04/07/2017
Loans
Keywords: Economic history; Economic policy; United States